2019
DOI: 10.1007/s40279-019-01055-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Catheterization on Artery Function and Health: When Should Patients Start Exercising Following Their Coronary Intervention?

Abstract: Coronary artery disease (CAD) is a leading cause of death worldwide, and percutaneous transluminal coronary angiography (PTCA) and/or percutaneous coronary intervention (PCI; angioplasty) are commonly used to diagnose and/or treat the obstructed coronaries. Exercise-based rehabilitation is recommended for all CAD patients; however, most guidelines do not specify when exercise training should commence following PTCA and/or PCI. Catheterization can result in arterial dysfunction and acute injury, and given that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 250 publications
(355 reference statements)
0
5
0
Order By: Relevance
“…In any event, the paradoxical constriction of catheterized arteries in response to exercise reported in these studies may contribute to exercise-induced myocardial ischemia postcatheterization (4). Indeed, endothelial damage following catheterization has been proposed as a factor to take into account when considering the optimal time to begin exercise rehabilitation (39).…”
Section: Discussionmentioning
confidence: 87%
“…In any event, the paradoxical constriction of catheterized arteries in response to exercise reported in these studies may contribute to exercise-induced myocardial ischemia postcatheterization (4). Indeed, endothelial damage following catheterization has been proposed as a factor to take into account when considering the optimal time to begin exercise rehabilitation (39).…”
Section: Discussionmentioning
confidence: 87%
“… 43 , 44 A study has shown that arterial dysfunction caused by catheterization recovers 4–12 weeks later, at this stage, patients are not yet able to fully engage in health behaviors. 45 With the recovery of arterial function, patients gradually adopt health behaviors that bring health benefits and meaning of life to patients. 44 This may be the reason why these determinants emerged in the last two interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous Coronary Intervention (PCI) is one of the therapy treatments that must be used in addition to evaluation for treating obstruction in coronary heart disease (PERKI, 2022). PCI is the most common CAD treatment and one of the most frequently performed medical procedures in the world with 97,376 PCI procedures reported in 2015 (Tryfonos et al, 2019). The European Society of Cardiology's recommendations for PCI in acute coronary syndrome advocate the transradial technique (TRA).…”
Section: Introductionmentioning
confidence: 99%